Global environmental governance and small states : architectures and agency in the Caribbean - Scobie, Michelle; Edward Elgar Publishing (Edward Elgar Pub., 2019)
This book provides an in-depth analysis of global environmental governance in the Anthropocene in the context of transformative environmental change and of the realities of Caribbean Small Island Developing States (SIDS). It explores the dynamic ways that global to local actors, institutions and norms relate to regional and local environmental policy, histories and contexts, and how this shapes future environmental outcomes for some of the most biodiverse regions of the planet. Global Environmental Governance and Small States fills a gap in the existing international relations and environmental governance literature. It explains how and where regional and local social, economic, geophysical, legal and historical contexts interact with global environmental governance architectures, norms and state and non-state actors, to determine the nature of SIDS' environmental perspectives, responses and policies. Using the Anthropocene as the historical context, the volume examines the most pressing issues for small states' perspectives and international responses to environmental challenges. Key among these are those associated with climate change, tourism, marine governance, energy security, cultural heritage and trade. This book will be an invaluable tool for academics and scholars of international relations, international politics, global environmental governance, international development, Caribbean affairs and regional governance. Its insights will also be of benefit for diplomats, development partners, policymakers and political actors working with and in Caribbean States, and SIDS, more widely.
Contents: 1. SIDS and environmental governance in the anthropocene -- 2. Thematic foundations of Caribbean environmental governance -- 3. Sustainable tourism governance and Caribbean SIDS -- 4. Climate change governance and Caribbean SIDS -- 5. Global marine and ocean governance and Caribbean SIDS -- 6. Renewable energy and energy security and Caribbean SIDS -- 7. Caribbean cultural and natural heritage governance -- 8. The global trade-environment nexus and Caribbean environmental governance -- 9. Key issues and emerging trends in Caribbean environmental governance and earth system governance research -- Index.
Includes index.
Description based on print record.
Keywords: Environmental economics -- Caribbean Area -- International cooperation; Environmental policy -- Caribbean Area -- International cooperation; Electronic books